Caplacizumab: an anti–von Willebrand factor antibody for the treatment of thrombotic thrombocytopenic purpura. (26th June 2020) - Hollifield, Alyssa L; Arnall, Justin R; Moore, Donald C
Abstract: Purpose: The pharmacology, pharmacokinetics, efficacy, safety, dosing and administration, and place in therapy of caplacizumab, a novel antibody fragment that inhibits von Willebrand factor, for the treatment of acquired thrombotic thrombocytopenic purpura (TTP) are summarized. Summary: Caplacizumab is a humanized anti–von Willebrand factor monoclonal antibody fragment that inhibits the interaction between ultralarge von Willebrand factor multimers and platelets. Caplacizumab is indicated for use in combination with standard-of-care modalities such as plasma exchange and immunosuppressive therapy for the treatment of adults with acquired TTP. By inhibiting von Willebrand factor, caplacizumab offers a new approach to the management of TTP by preventing the development of potentially life-threatening microvascular thrombosis that can occur in the disease process. In a randomized, placebo-controlled phase 3 trial, patients with acquired TTP treated with caplacizumab had more rapid platelet level normalization than placebo users; caplacizumab use also resulted in lower rates of disease recurrence and TTP-related death. The most common adverse events associated with caplacizumab use are bleeding-related events. In a phase 3 trial, serious bleeding-related adverse events were reported in 8 patients (11%) in the caplacizumab group and 1 patient (1%) in the placebo group. Caplacizumab is administered as an 11-mg intravenous loading dose 15 minutes prior to plasma exchange, followed by administration of 11 mg subcutaneously daily after plasma exchange. Once-daily caplacizumab administration can be continued for 30 days after the last plasma exchange. The medication and supplies for administration are provided as a single-use kit; patients should be trained on proper reconstitution and self-administration technique prior to the use of caplacizumab in the ambulatory setting. Conclusion: Caplacizumab is a first-in-class von Willebrand factor inhibitor approved for the treatment of adults with acquired TTP.